Reproductive Biology of the Short-Necked Clam, Paphia undulata (Born 1778) from Southern Negros Occidental, Central Philippines - Nabuab, Fenelyn M.; Fernandez, Leah Ledesma; Campos, Anabelle del Norte (Science Diliman: A Journal of Pure and Applied Sciences; Vol 22 No 2 (2010))
The short-necked clam, Paphia undulata , occurs in coastal muddy bottoms of Hinigaran, Binalbagan, and Himamaylan, Negros Occidental where it has an important contribution to fisheries. However, stocks in these areas are dwindling and in order to formulate sound management strategies, information on the reproductive biology of this species is a prerequisite.   Also, knowledge on the reproduction of this species is a prelude to its laboratory breeding and rearing. Reproductive biology of the short-necked clam from the three areas was studied over an annual cycle. Short-necked clams were collected monthly from catches of compressor divers. Five gonad stages were described based on histological examinations: developing, mature, partially spawned, redeveloping, and spent. Immature or indeterminate gonads were also noted. Although occasional presence of hermaphrodite gonads was observed this species is still functionally dioecious with 1.00M: 1.02F sex ratio.    Sexual maturity is attained at 42.6 mm for males and 44.8 mm for females. Short-necked clams have continuous breeding season.  However, peak of spawning activities is on the months of August to November which coincide with the monsoon transition months probably due to the decrease in salinity and nutrient influx during these months.  Organisms smaller than 45mm must not be collected and collection must be regulated during peaks of spawning activities to leave a portion of reproductively mature individuals to ensure sustainability of fisheries. However, in terms of laboratory breeding and rearing of this species, it is fundamental to consider the spawning peaks and size at sexual maturity to ensure successful spawning in the laboratory. Hence, broodstock to be used in the experiments must be sexually mature (>45mm) and collected during peaks of spawning activities.
Keywords: Paphia undulata, reproductive biology, gonad stages, dioecious, size at sexual maturity, continuous breeding season, sustainability of stocks